The role of TSC2 in breast cancer: a literature review - Zhu, Qiao-Yan; He, Zhe-Min; Cao, Wen-Ming; Li, Bei (Frontiers in Oncology, 2023)
TSC2 is a tumor suppressor gene as well as a disease-causing gene for autosomal dominant disorder tuberous sclerosis complex (TSC). Research found that tumor tissues have lower TSC2 expression levels than normal tissues. Furthermore, low expression of TSC2 is associated with poor prognosis in breast cancer. TSC2 acts as the convergence point of a complex network of signaling pathways and that receives signals from PI3K, AMPK, MAPK, and WNT pathways. It also regulates cellular metabolism and autophagy through inhibition of mechanistic target of rapamycin complex, which are processes relevant to the progression, treatment, and prognosis of breast cancer. In-depth study of TSC2 functions provides significant guidance for clinical applications in breast cancer, including improving the treatment efficacy, overcoming drug resistance, and predicting prognosis. In this review, protein structure and biological functions of TSC2 were described and recent advances in TSC2 research in different molecular subtypes of breast cancer were summarized.